Financial policies and everyday life - Tarapore, S.S (New Delhi Academic foundation, 2010)
After a long career in central banking, the distinguished economist S.S. Tarapore has been writing columns in financial dailies. There was a felt need to reach out to a wider audience in a regional language. During the period October 2005-August 2008, he turned to writing a regular column in the widely circulating Gujarati newspaper, the Divya Bhaskar. This volume brings to the English speaking readers, for the first time, his writings in the Divya Bhaskar on monetary, fiscal, banking and external sector management, but essentially from the viewpoint of the aam aadmi. The volume would be of interest to the general reader who wishes to stay abreast of developments in financial policies and it would also be of interest to policymakers, opinion makers, bankers, academics and students.
Keywords: People with social disabilities-Government policy-India